Islam and Ethnicity in Africa and the Middle East - Aftab A. Khan (International Institute of Islamic Thought, 1991)
This three-day seminar, sponsored by the State University of New York at Binghampton's Schweitzer Chair in Humanities, the South Asian and African Studies Program, the Department of African Studies, and the African American Institute, discussed the African experience, the Middle East experience, and crosscultural comparison. The opening presentation was made by Ali Mazrui, who holds the Schweitzer Chair in Humanities at Binghampton. He discussed the interaction of Islam and ethnic cultures in Africa and pointed out that Islam and ethnicity are essentially contradictory concepts, one being a universalist and the other a particularist view of society. "But," according to him, "Islam has become ethnicized and ethnicity tends to become Islarnized." The resulting tensions can be overcome only by a strong sense of human solidarity, such as the one which the Prophet talked about when he said that nobody excels in faith unless he loves for his brother what he loves for himself ...